Gambaran sikap dan pencegahan guru SD Kristen Tabita 2 Manado terhadap tindak kekerasan pada anak usia sekolah - Yacub, Fatihasari; Ottay, Ronald; Siagian, Iyone E. T. (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2016)
Violence in school age children according to the Convention of The Regulation of Whaling (ICRW) in 2015 reached 84% in Indonesia. Benefits of the research is to improve the ability of the author, information data and reference materials further research, and as a source of data for the Ministry of Women's Empowerment and Child Protection (Ministry PPA). The purpose of this study was conducted to determine the attitudes and prevention picture Christian elementary school teacher Tabitha 2 Manado. Methods This study included descriptive study using qualitative techniques. Population taken 10 teachers, eight teachers to follow in-depth interviews, six focus group discussions following the teacher aged 35 to 57 years. The results obtained by the attitude of some teachers have counseled child victims of violence and perpetrators of violence. Prevention agreed by all the teachers, the religious approach. The conclusion is based on in-depth interviews and Focus Group Discussions (FGD) attitude and the prevention of an elementary school teacher Christian Tabita 2 Manado ie they will ask first the problem and then follow up the issue with the report to the authorities as to prevent them going to do a religious approach and more often membingbing children -child. Suggestions necessary role of government to be more given the socialization of violence.